Cluster Analysis of the Productivity of Nurses’ Work - Hermansyah Hermansyah; Agung Riyadi; Rina Delfina (Fakultas Ilmu Keperawatan Universitas Indonesia, 2022)
Productivity is a measure of performance, including effectiveness and efficiency. The importance of work productivity for nurses includes its evaluation role in contributing to continuous improvement. The purpose of this study is to determine the classification of nurses in clusters based on work productivity in the inpatient room. It is an analytic study with a cross-sectional design. The study sample were 130 nurses in the inpatient room at the Bengkulu Provincial Hospital, selected using the proportional random sampling technique. A questionnaire was employed for the data collection. Data analysis was performed univariately, and multivariately with cluster analysis. The study results involved clusters I-III, which comprised nurses with high, medium and low work productivity. The variables of motivation, management, work environment, achievement opportunities, work climate, income, workload, work ethic, and work discipline have a significant effect on the formation of the cluster (p < 0.001). Cluster I comprised 69 nurses, cluster II 53 nurses and cluster III eight. A need is shown for clarity of organizational structure, job descriptions, the granting of authority and responsibility, creation of a work system that encourages innovation, provision of facilities, clarity of Nursing Care Standard (NCS), work guidelines, and Standard Operational Procedure (SOP). Abstrak Analisis Klaster Produktivitas Kinerja Perawat. Produktivitas merupakan salah satu alat ukur kinerja, termasuk efektivitas dan efisiensi. Produktivitas menjadi penting bagi perawat karena menjadi tolak ukur dalam evaluasi untuk perbaikan yang berkelanjutan. Tujuan penelitian ini adalah untuk mengetahui klasifikasi perawat dalam klaster berdasarkan produktivitas kerja di ruang rawat inap dengan menggunakan jenis penelitian analitik dan desain studi cross-sectional. Sampel pada penelitian adalah 130 perawat pelaksana di ruangan rawat inap di Rumah Sakit Provinsi Bengkulu, diambil dengan teknik proportional random sampling. Pengumpulan data menggunakan kuesioner. Analisis data dilakukan secara univariat dan multivariat dengan analisis klaster. Hasil penelitian terdiri dari klaster I-III yang menunjukkan perawat dengan produktivitas kerja tinggi, sedang, dan rendah. Variabel motivasi, manajemen, lingkungan kerja, kesempatan berprestasi, iklim kerja, penghasilan, beban kerja, etos kerja, dan disiplin kerja berpengaruh signifikan terhadap terbentuknya klaster (p < 0,001), dan jumlah anggota klaster I adalah 69 perawat pelaksana, jumlah anggota klaster II adalah 53 perawat pelaksana, sedangkan jumlah anggota klaster III adalah 8 perawat pelaksana. Perlunya kejelasan struktur organisasi, uraian tugas, pemberian wewenang, dan tanggung jawab, dapat menciptakan sistem kerja yang mendorong inovasi, penyediaan fasilitas yang mendukung kinerja, kejelasan standar asuhan keperawatan, pedoman kerja, dan standar operasional prosedur. Kata Kunci: analisis klaster, perawat, produktivitas kerja